Formation of novel photoluminescent hybrid materials by sequential vapor infiltration into polyethylene terephthalate fibers. Issue 23 (21st November 2014) - Akyildiz, Halil I.; Lo, Michael; Dillon, Eoghan; Roberts, Adam T.; Everitt, Henry O.; Jur, Jesse S.
Abstract: Abstract : Fibrous polyethylene terephthalate (PET) was modified by organometallic vapor exposure to form hybrid materials with unique photoluminescent characteristics. Using a sequential vapor infiltration (SVI) process, the elongated exposures of trimethylaluminum (TMA) to PET were examined. As the infiltration temperature increased, the evidence of changes in the reaction between the organometallic vapor and the polymer was observed as well as significant changes in the infiltration depth into the polymer fiber, owing to the variation in the reaction mechanisms of the hybrid material formation. At TMA exposures of 60 °C, the mass of the polymer fiber increased by ∼55 wt%, whereas exposures at 150 °C were limited to ∼25 wt% infiltration. Photoluminescence analysis of PET after TMA infiltration shows an intensity increase of up to ∼13x and an increase in red shift with increasing infiltration temperature, attributed to the variations in the reaction mechanism to form the hybrid modification observed through the spectroscopy analysis.